"The Pause": A Delphi Methodology Examining an End-of-Life Practice. (October 2019) - Cunningham, Tim; Ducar, Dallas M.; Keim-Malpass, Jessica
"The Pause" was first practiced by a nurse at a Level 1 trauma center to honor the death of a deceased patient. This practice has spread internationally and is used in emergency departments, intensive care, transplant, and oncology units, in addition to pre-hospital settings. There is a paucity of research published on the effects of The Pause for health care workers. We used a three-staged Delphi methodology to understand the barriers, benefits, and language used in The Pause. Analyses of email communication and interview transcripts suggest that The Pause poses minimal risk and has considerable benefits. Benefits include increased perceived team cohesion, a moment for reflection, and a method by which to honor a deceased patient. The Pause allows nurses to feel more present to meet the needs of the next patient they care for during a shift. Further research is merited.